A RealTime Interactive MultiView Video System - Lou, Jian-Guang; Cai, Hua; Li, Jiang (ACM Multimedia (full paper), 2005)
With the rapid development of electronic and computing technology, multi-view video is attracting extensive interest recently due to its greatly enhanced viewing experience. In this paper, we present the system architecture for real-time capturing, processing, and interactive delivery of multi-view video. Unlike previous systems that mainly focus on multi- view video capturing, our system is designed to provide multi-view video service with high degree of interactivity in real time, which is still challenging in the current state of the technology. The proposed architecture tackles many practical problems in system calibration, object tracking, video compression, interactive delivery, etc. With the proposed system, users can interactively select their desired viewing directions and enjoy many exciting visual experiences, such as view switching, frozen moment and view sweeping, in real-time and with great freedom.